Science and security expertise: Authority, knowledge, subjectivity. Issue 84 (August 2017) - Rychnovská, Dagmar; Pasgaard, Maya; Berling, Trine Villumsen
Abstract: What role does science play in shaping the political? This themed issue brings together scholars from political science, human geography, natural science and related fields with the common aim of exploring links between science/expertise and politics with a specific focus on security implications. The increasing attention to threats and risks related to issues such as climate change, migration, energy security, or emerging technologies creates a demand for new types of experts and expertise relevant for security politics. By looking at the actors who operate at the boundary between science, bureaucracy and security politics, this themed issue seeks to destabilize the notion of an apolitical sphere of science and expertise, while at the same time demonstrating how the politics of expertise shapes the authority and subjectivity of scientists and reconfigures the meanings and roles of scientific knowledge. In this editorial, we connect relevant literatures and introduce the individual articles that compose the themed issue.